Effect of Soil Copper and Foliar Copper Applications on Micronutrient Contents of Tomato Plants - SONMEZ, SAHRIYE; KAPLAN, MUSTAFA; KEMAL SONMEZ, N.; KAYA, HARUN; UZ, ILKER (Asian Journal of Chemistry, 2010)
In this study, effects of both soil copper applications (SCuA) and foliar copper application (FCuAF) on micronutrient contents (copper, iron, manganese and zinc) of tomato plants were investigated. For this purpose, Cu was applied as a factorial combination of rate (0 [S1], 1000 [S2] and 2000 mg kg-1 [S3], soil) and frequencies (no application[F1], biweekly [F2] and weekly [F3], foliar). Two separate experiments were conducted to observe effects of different Cu containing chemicals. Two fungicides, Gunner and Tenn-Cop 5E (containing Cu oxychloride and copper salts of fatty and rosin acids, respectively), were used for foliar copper applications. CuSO4·5H2O was used to provide to soil. Both in the experiment-I (Gunner, Cu oxychloride) and in the experiment II (Tenn-Cop 5E, copper salts of fatty and rosin acids), Cu and Mn contents of plant samples increased with increasing of SCuA and FCuAF. Fe contents of leaf and fruit samples were affected by SCuA and decreased with increasing of SCuA. Root Fe content generally decreased with increasing of both SCuA and FCuAF. Leaf, fruit and root Zn contents were affected by both SCuA and FCuAF and Zn contents of plant samples decreased with increasing SCuA and FCuAF. As a result, both SCuA and FCuAF, especially aiming to control plant diseases, showed different effects on Cu, Fe, Mn and Zn contents of tomato plants. It was determined that, by taking into account the amount and frequency of applications, the Cu doses applied either to soil or leaf were too high. Thus, it would be useful to conduct more in detailed studies to determine Cu toxicity limits on tomato plants at different soil pH levels by gradually decreasing Cu doses.